Alcohol and Breastfeeding: What do Australian mothers know? - Giglia, Roslyn; Binns, Colin (Wiley, 2007)
Background: Drinking alcohol during pregnancy can cause many birth defects and developmental disabilities. There is considerable information available for pregnant women regarding the dangers of drinking alcohol during this time. Postpartum many women enter the period of lactation, which can last for several months to years. However information regarding safe levels of alcohol consumption during lactation is limited despite potential harmful effects on infant development and maternal lactational performance. Methods: A descriptive study using qualitative methods. Data was collected in focus groups interviews conducted from February 2004 to December 2005. Women eligible to participate in the focus groups were currently breastfeeding or had been breastfeeding within the previous 12 months.Results: Seventeen women aged 28 to 41 years participated in postpartum focus groups. The mothers were largely unaware of the effects of alcohol on breastfeeding performance and the development of the infant. The majority of the women in the focus groups expressed concern at the lack of information available regarding ‘safe’ alcohol consumption practices during lactation and reported being more diligent during pregnancy with regard to abstaining from alcohol. Conclusion: There is a variable level of knowledge regarding consuming alcohol and breastfeeding among Australian mothers. The majority of participants were aware of the recommendations regarding alcohol during pregnancy and felt that a similar level of information was required to provide direction and support during lactation.